Health Communication Revolution Through Content: Multi-Step Flow and More Spill Over of Communication - Ani Herna Sari; Rahma Sugihartati; Nur Wulan; Afifatur Rohimah (Nyimak: Journal of Communication, 2022)
Health communication has undergone a revolution since the advent of social media, health content is no longer a tool for disseminating health information by medical or health personnel, but has become content that is easily produced by the general public. The purpose of this study is to uncover the implementation of the health revolution through Instagram content. Phenomenological research methods with content analysis, which is strengthened by data mining through Focus Group Discussions and interviews. The results showed that social media made health communication undergo a revolution. The communication process that is formed is a multi-step flow of communication (many stages), even the circulation of information forms a layer layer of stages in communication becomes irregular. This makes people experience more spill over of communication, which changes the culture of health communication in society.Keywords: The revolution of health communication, content, information sharing, social media ABSTRAKKomunikasi kesehatan telah mengalami revolusi sejak hadirnya media sosial, konten kesehatan tidak lagi menjadi alat penyebaran informasi kesehatan oleh tenaga medis atau kesehatan, tapi sudah menjadi konten yang dengan mudah diproduksi oleh masyarakat umum. Tujuan penelitian ini mengungkap implementasi revolusi kesehatan melalui konten instagram. Metode penelitian fenomenologi dengan analisis konten, yang diperkuat dengan penggalian data melalui Focus Group Discussion dan wawancara. Hasil penelitian menunjukkan bahwa media sosial membuat komunikasi kesehatan mengalami revolusi. Proses komunikasi yang terbentuk adalah multi step flow of communication (banyak tahap), bahkan peredaran informasinya membentuk layer layer tahap dalam komunikasi menjadi tidak teratur. Hal ini membuat masyarakat mengalami more spill over of communication (peluberan informasi yang berlebihan), yang merubah budaya komunikasi kesehatan di masyarakat.Kata Kunci: Revolusi komunikasi kesehatan, konten, peluberan informasi, media sosial